EFEKTIVITAS SALAT TAUBAT DALAM MENINGKATKAN KETENANGAN HATI - Ahmad Rusdi (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2016)
The purpose of this study is examine the prayers of repentance effect on sobriety. Respondents of this study are 49 Students. This research was conducted by using a simple experiment. Researchers have explained how the prayers of repentance to be done during one week. sobriety was measured before and after one week. sobriety consists of two aspects, composure (al-suku>n) and conviction (al-yaqi>n). After prayers of repentance for one week, sobriety on respondents increased significantly (Sig 0,00) both aspects, al-suku>n (Sig 0,00) and al-yaqi>n (Sig 0,036). Some details of the results of this study showed unique results. This study concluded that multidimensional prayers of repentance will increase sobriety periodically.